The Using of The Cone Bag and The Satisfaction of Delivery Assistants in Measuring Post Partum Bleeding - Anita, A; Purwati, P; Kodri, K; Hernani, Nani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
The maternal mortality rate in Indonesia in 2015 was 305/100,000, which was still below the WHO target of 102/100,000, with the leading cause of death was postpartum haemorrhage. The delay in diagnosis can be caused by a delay in diagnosing postpartum bleeding due to errors in measuring blood loss. The purpose of this study was to determine the satisfaction of birth attendants in measuring postpartum haemorrhage using a cone bag so that the diagnosis of postpartum haemorrhage can be made correctly. This research aims to produce a product in the form of a cone bag as a measuring tool for postpartum haemorrhage. This type of research is a quantitative, quasi-experimental analytical research design. The study was conducted on 60 birth attendants in hospitals/health centres/maternity clinics in Bandar Lampung. The analysis used the T-test. The statistical analysis results showed an effect of the use of a cone bag on the satisfaction of birth attendants in measuring postpartum haemorrhage (p = 0.000). Birth attendants can use cone bags to measure postpartum haemorrhage. Hospitals/health centres/maternity clinics can facilitate cone bags to measure postpartum haemorrhage to provide job satisfaction for birth attendants (nurses/midwives/doctors).Abstrak: Angka kematian ibu di Indonesia tahun 2015 sebesar 305/100.000 masih berada dibawah target WHO 102/100.000, dengan penyebab utama kematian perdarahan post partum. Keterlambatan mendiagnosis dapat disebabkan oleh keterlambatan diagnosis perdarahan post partum, dikarenakan kesalahan dalam pengukuran jumlah darah yang hilang. Tujuan penelitian adalah untuk mengetahui kepuasan penolong persalinan dalam pengukuran perdarahan post partum dengan menggunakan kantung kerucut, sehingga dapat menegakkan diagnosis perdarahan post partum dengan tepat. Target penelitian ini adalah dihasilkannya produk berupa kantong kerucut sebagai alat ukur perdarahan post partum. Jenis penelitian kuantitatif, rancangan penelitian analitik quasi eksperimen. Penelitian dilakukan terhadap 60 responden penolong persalinan di Rumah Sakit/puskesmas/klinik bersalin di Bandar Lampung. Analisis menggunakan uji T. Hasil analisis statistik diperoleh ada pengaruh penggunaan kantung kerucut terhadap kepuasan penolong persalinan dalam pengukuran perdarahan post partum (p=0,000). Penolong persalinan dapat menggunakan kantung kerucut dalam mengukur perdarahan post partum, RS/Puskesmas/klinik bersalin dapat memfasilitasi alat kantung kerucut dalam mengukur perdarahan post partum sehingga memberikan kepuasan kerja dari penolong persalinan (perawat/bidan/dokter).